2010
DOI: 10.1143/jjap.49.08jf07
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Supermagnetron Plasma Chemical Vapor Deposition of Hydrogenated Amorphous Carbon Nitride Films

Abstract: The design, construction and operation of a compact, high-efficiency Bragg diffraction spectrometer are described. An accurate method of alignment is presented. The spectrometer has been tested with a lead stearate analysing crystal by measuring carbon K (methane) and argon L x-ray energies produced by direct electron beam excitation. The high efficiency of this apparatus is demonstrated by measuring satellite lines of the neon K spectrum with a RbAP analysing crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…A pulsed RF supermagnetron plasma CVD apparatus was used for the deposition of a-CN x :H films [12], as shown in Figure 1. The amplitude of one of the two RF power sources with the same RF frequency of 13.56 MHz was modulated using a pulse generator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulsed RF supermagnetron plasma CVD apparatus was used for the deposition of a-CN x :H films [12], as shown in Figure 1. The amplitude of one of the two RF power sources with the same RF frequency of 13.56 MHz was modulated using a pulse generator.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in substrate temperature degraded the character of the a-CN x :H films. By using RF powers modulated by a 2.5-kHz pulse frequency and a duty ratio (defined as the ratio of pulse on-time to total cycle time) of 12.5%, in the case of supermagnetron plasma CVD, the substrate was cooled stably and relatively hard and homogeneous a-CN x :H films were obtained [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their properties are strongly dependent on the deposition techniques employed in their fabrication [1][2]. Most a-CN x films prepared by chemical vapor deposition (CVD) have a nitrogen concentration of less than 0.3, and exhibit high hardness, optical transparency, and high resistivity [3][4][5][6][7]. In contrast, a-CN x films prepared by physical vapor deposition (PVD) have a higher nitrogen concentration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To suppress substrate heating resulting from the bombardment of high-energy ions, periodic plasma deposition has been found to be effective [21]. Several studies have shown PRF plasma CVD to be effective for the deposition of low-residual-stress a-CN x :H films [21] [22] [23]. Low-residual-stress films might be effective for use in electronic devices, such as vacuum field emitters and photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%